The Post-Reform Bid-Ask Spread Disparity between Nasdaq and the Nyse - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2003)
We report further evidence of the difference in execution costs between Nasdaq and the NYSE before and after the 1997 market reforms. We find that informed trading costs are consistently higher on Nasdaq both before and after the reforms. In the pre-reform period the Nasdaq-NYSE disparity in bid-ask spreads cannot be completely attributed to the difference in informed trading costs. However, in the post-reform period the spread difference between these two markets becomes insignificant with the effect of informed trading costs controlled. Our findings are consistent with the contention that the reforms have largely reduced noninformation trading costs and dealers' rents.